The Intersection of Black Lives Matter and Adult Education: One Community College Initiative. Issue 150 (June 2016) - Miller, Brian; Schwartz, Joni
Abstract : This chapter is a call to action for adult educators to critically engage the Black Lives Matter Movement through pedagogy, community engagement and scholarly activism. It explores the intersection of the Black Lives Matter movement and adult education by highlighting the response of one community college initiative.